Penerapan Model Discovery Learning Melalui Latihan Soal Terbimbing Sebagai Upaya Meningkatkan Hasil Belajar Matematika Peserta Didik pada Pokok Bahasan FBB dan KPK di Kelas IV SDN 03/X Tanjung Solok Semester Ganjil Tahun Ajaran 2021/2022 - Usman Usman (Departement of Mathematics Education, 2022)
This study aims to describe and obtain information on improving Mathematics learning outcomes through Discovery Learning. This research is a classroom action research consisting of two cycles, each cycle consisting of two meetings. Each meeting consists of four stages, namely planning, implementation, observation and reflection. The subjects of this study were the fourth grade students of SDN 03/X Tanjung Solok, totaling 25 people. This research was conducted in the odd semester of the 2021/2022 academic year. Data collection techniques using tests, observations, and documentation. Data were analyzed using percentages. The results of the study indicate that through Discovery Learning, students can improve their Mathematics learning outcomes in class VI SDN 03/X Tanjung Solok by giving rewards.